Integration and team performance in the NBA - Olsen, A.; Leeds, M. A. (Journal of Sports Economics, 2024)
The causes and effects of the integration of the NBA have received far less attention than the integration of other sports. We use survival analysis to examine whether integration was led by successful franchises or unsuccessful teams. We then go on to examine the contributions of Black players in the 1950s and early 1960s. Specifically, we ask whether teams that relied more heavily on Black players were more successful, as was the case in baseball. We also examine the degree to which individual Black players contributed to their teams.